An anonymous secure authentication method for tourist attraction network-based edge computing - Zhou, Xuefan; Zhuang, Zhaoyu (Frontiers in Physics, 2025)
An elliptic curve cryptography (ECC)-based anonymous authentication mechanism is designed to meet the demand for lightweight, anonymous, and trustworthy authentication for tourist attraction networks in edge computing environments. This mechanism uses pseudo-randomly generated identities to cover the real identity of the tourists, which ensures the anonymity of the scheme. The security of mutual authentication between the tourist and the edge computing server is increased with the help of smart card technology. At the same time, the mechanism also has the ability to guarantee security in case of smart card theft. The introduction of timestamps effectively enhances the scheme’s ability against a replay attack. The security of the scheme is analyzed using Burrows—Abadi—Needham (BAN) logic and non-formal analysis methods. Finally, the results of a comprehensive analysis and comparison show that the scheme has high practical value.